Low cost country (LCC) sourcing – A study of critical factors for a sustainable business and operating model - Kolekar, Parshuram Laxman (2021)
Problem: Companies are trying to find the best ways to optimise their sourcing or manufacturing cost. Low Cost Country Sourcing (LCCS) has become a buzzword. Although a few companies have adopted this approach but only few are able to realise the full benefit of this approach due to lack of knowledge, several unknown factors that are ignored before entering into LCC, a missing organisation level vision and strategy, organisation structure, structured execution etc. Therefore, it is an important matter to understand the factors that are influencing LCC decision making and the factors that are enablers or key success factors for LCC sourcing.